Quick Homework Help

# m= -2n - 2 3m - 2n = 10 ⚑ Flag

by alex865 at November 04, 2010

body, td, input { font-family:arial; font-size:16px; } #container { padding:5px 20px; } #header h2 { font-size:27px; color:#d0d0d0; margin: 22px 0 10px; } #searchform { width:470px; margin:0; } #searchform input { font-size:18px; border: 1px solid #aaa; color:#aaa; } #searchform input:hover, #searchform input:focus, #searchform input:active { border: 1px solid #888; color:#000; } #searchform input.searchbox { padding:4px; width:300px; } #searchform input.searchbutton { padding: 3px 10px; color:#000; } #searchform div.poweredby { float:right; width:80px; text-align:center; } #searchform div.poweredby span { font-size:10px; } #searchform div.poweredby img { so you take m=-2n-2 and plug it into your other equation:3(-2n-2)-2n=10now you can simplify:-6n-6-6n=10-12n-6=10-12n=16n=16/-12n=-1.3333

brandy043 November 04, 2010

Plug in to get 3(-2n-2)-2n=10 so -6n-6-2n=10,-8n-6=10 add 6 so -8n=16 divide, to get n=-2 then plug in -2 to get m= 2

What_ok November 04, 2010

3(-2n-2)-2n=10-6n+6-2n=10-8n=-4n=1/2 m=-2(1/2)-2m=-1-2m=-3

gibby. November 07, 2010